Malignant Edema in Horse by Clostridium perfringens Type A - Ferreira Junior, Jair Alves; Silveira Silva, Rodrigo Otávio; Faria Lobato, Francisco Carlos; Teixeira Neto, Antônio Raphael; Nascimento, Karla Alvarenga; Almeida e Macedo, Juliana Targino Silva; Pedroso, Pedro Miguel Ocampos (Acta Scientiae Veterinariae, 2020)
Background: Malignant edema is one of the terms used to designate severe necrotizing syndromes in soft tissues by Clostridium spp. which are potentially fatal in farm animals. These species are responsible for myonecrosis, belonging to the group of histotoxic clostridia, and may also culminate in toxemia with the worsening of the lesions. These clostridia and their spores require a gateway such as wounds on mucous membranes or skin, which may occur due to shear, tail cut, injuries during delivery, castration or injections by contaminated needles. This report aims to describe the clinical-pathological findings of a case of malignant edema caused by C. perfringens type A in an equine. Case: A female equine, undefined breed, used as traction animal, had a history of abdominal pain. According to the requisitioning veterinary, the tutor reused needles for medication. On palpation, a compact mass was noticed in the pelvic flexure, as well as edema on the region of head and neck with crackling areas. After surgical intervention for compactation correction, the animal did not show anesthetic recovery and was submited to euthanasia. Tissue samples were collected, fixed in 10% buffered formalin solution, routinely processed for histopathology and stained with hematoxylin and eosin and Gram stain. Samples of serous-sanguineous edema fluid and fragments of the abdominal muscles and neck were collected. The samples were kept under refrigeration and sent for microbiological culture. Necropsy showed the subcutaneous region of the pectoral was markedly gelatinous and yellowish (edema) and subcutaneous emphysema characterized by accumulation of serous-sanguineous fluid and gas bubbles. In microscopy, we verified fibrous-haemorrhagic, emphysematous, suppurative and diffuse superficial histiocytic necrotizing cellulitis and myositis. Gram-positive bacillary aggregates were observed in spleen and subcutaneous sections. Colony suggestive of Clostridium perfringens were submitted to PCR for confirmation of identity followed by genotyping. Lastly, C. perfringens type A was isolated from the muscle fragments and serosanguinolent liquid collected. Discussion: In the present study, the diagnosis of malignant edema caused by Clostridium perfringens type A in an equine was confirmed by the clinical-pathological findings added to the isolation and genotyping of the agent from fragments of injured muscle. Although C. perfringens has been reported in cases of clostridial myositis in horses in the United States, in Brazil there are only reports of sporadic cases associated with C. septicum, C. novyi and C. chauvoei in this species. In histotoxic cases by C. perfringens, alpha toxin is known to be the main virulence factor involved, causing destruction of the phospholipid membrane of erythrocytes, endothelial cells, leukocytes and muscle fibers. As consequence, there is an increase in the vascular permeability of capillaries and, with the spread of the infection, there is production of inflammatory edema with serosanguineous exudate and gas. Typically, anatomopathological findings are characterized by increased volume of the affected region associated with edema with bloody fluid and rancid odor, gas bubbles in the subcutaneous tissue, and fasciae associated or not with necrotic myositis. It is assumed that a contaminated needle injection, performed during the treatment of colic symptoms on the property has been the gateway to infection. The clinical course of clostridial infection in horses is considered acute, ranging from 24 to 48 h. In this case, was observed the animal with signs of cervical and pectoral edema still in the property, a day before euthanasia. This is the first study to confirm Clostridium perfringens as a cause of gas gangrene in horses in Brazil.